2020
DOI: 10.1038/s41598-020-62990-0
|View full text |Cite|
|
Sign up to set email alerts
|

Heavy reliance on plants for Romanian cave bears evidenced by amino acid nitrogen isotope analysis

Abstract: Heavy reliance on plants is rare in carnivora and mostly limited to relatively small species in subtropical settings. The feeding behaviors of extinct cave bears living during Pleistocene cold periods at middle latitudes have been intensely studied using various approaches including isotopic analyses of fossil collagen. In contrast to cave bears from all other regions in Europe, some individuals from Romania show exceptionally high δ 15 n values that might be indicative of meat consumption. Herbivory on plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…From a biomolecular perspective, traditional isotopic methods based on δ 15 N and δ 13 C from bulk protein (collagen), and more recently δ 15 N analyses of individual amino acids, were used to reconstruct the cave bear's dietary preferences. These studies essentially support a herbivorous diet across its range [41][42][43][44][45]. Palaeogenomic studies have revealed a complex evolutionary history within the cave bear species complex with three major groups: the Caucasian group including praekudarensis and kudarensis taxa; the European group including spelaeus, ingressus, eremus, and kanivetz from the Ural Mountains; and the Ural-specific group made up by rossicus [40].…”
Section: Cave Bearsmentioning
confidence: 81%
See 1 more Smart Citation
“…From a biomolecular perspective, traditional isotopic methods based on δ 15 N and δ 13 C from bulk protein (collagen), and more recently δ 15 N analyses of individual amino acids, were used to reconstruct the cave bear's dietary preferences. These studies essentially support a herbivorous diet across its range [41][42][43][44][45]. Palaeogenomic studies have revealed a complex evolutionary history within the cave bear species complex with three major groups: the Caucasian group including praekudarensis and kudarensis taxa; the European group including spelaeus, ingressus, eremus, and kanivetz from the Ural Mountains; and the Ural-specific group made up by rossicus [40].…”
Section: Cave Bearsmentioning
confidence: 81%
“…Few studies thus far have combined isotopes and aDNA to shed light on cave bear's ecology, evolutionary history, and extinction [45,49,60,61] (Figure 3).…”
Section: Cave Bearsmentioning
confidence: 99%
“…This is, however, true in the case of a single food web. In more complex ecosystems, the particular food webs which rely on different resources may exhibit different isotopic signatures of equivalent trophic levels ( 63 ). Our result is in line with the isotopic relationships observed in modern ecosystems that include agricultural biotopes ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen stable isotopes from Beringia 18 (δ 13 C − 18.27 ± 0.4‰, δ 15 N 8.5 ± 1.02‰) and British Columbia 34 (δ 13 C − 18.9‰, δ 15 N 10.6‰) are suggestive of a high trophic position with terrestrial meat consumption, especially caribou 20 . However, definitive calculation of trophic position, particularly in the case of omnivorous mammals that readily consume meat and plant material, must rely on future analyses of compound specific stable isotopes of individual amino acids and larger sample sizes 47 , 48 . Brown bears, U. arctos , tend to consume more animal protein at northern latitudes 49 , and coastal populations in Alaska today exhibit stable isotope values with more positive carbon values than that of the CCI A. simus , reflecting more marine protein consumption (δ 13 C − 15.46 ± 2.04‰, δ 15 N 10.79 ± 4.15‰; Suess corrected 18 ).…”
Section: Discussionmentioning
confidence: 99%